The development of the digital teaching competence from a sociocultural approach - Colás-Bravo, Pilar; Conde-Jiménez, Jesús; Reyes-de-Cózar, Salvador (Comunicar, 2019)
Many Nowadays, digital teaching competence transcends the individual training of teachers in ICT The European framework DigCompEdu, highlights that teachers must train students in the application of digital technologies in a critical and responsible way, in terms of information, communication, content generation, wellbeing and problem solving. Despite the good intentions to systematize a common model of development of digital competence, it is detected that the proposals lack a pedagogical approach that serves as a theoretical framework for them. This paper proposes a development model of the digital teaching competence based on the sociocultural approach through four constructs: Command, Preference, Reintegration and Appropriation. For this study, an ad hoc scale is created to record the digital teaching competence through the development of this in their students and empirical evidences are provided. A survey type design is proposed. The sample consists of 1,881 students of compulsory education in Andalusia (Spain). SPSS is used to analyse data. The average general results for each of the dimensions studied reveal a medium level of development of digital competence. It is concluded that there is still too much to be done in terms of teacher training in ICT, being necessary to provide them strategies for the development of this in their students.